Sociology : a brief introduction - Schaefer, Richard T. (McGraw-Hill, 2012)
Helps students take sociology with them on campus, in their careers, and in their communities. Through coverage of globalization, race and ethnicity, careers in sociology, and topics like mass media and social policy, this book provides students with knowledge they can use at school, at work, in their neighborhoods, and in the global community